Efforts to Improve Scientific Literacy Capabilities in Indonesia: Systematic Literature Review - Mujakir Mujakir; Nurmalahayati Nurmalahayati; Safrijal Safrijal; Putroe Salsabil; Eni Fatma; Zainuddin Zainuddin (CV FOUNDAE, 2024)
Science literacy is an essential skill needed by students to face the challenges of globalization and technological development. However, the level of science literacy in Indonesia is still below international standards. The aim of this research is to know the efforts that can be made to improve science literacy skills. The method used is a systematic literature review (SLR). The Scopus database was used to search for the reviewed articles. Scientific literacy was used as the search keyword and limited to the last 5 years. A total of 26 articles were obtained from the screening process out of 1355 documents. The collected literature was then analyzed qualitatively. The findings show that the integration of technology such as Virtual Reality (VR) and e-learning platforms has great potential in enhancing students' understanding and engagement in science literacy. In addition, innovative pedagogical approaches, such as project-based learning and STEAM (Science, Technology, Engineering, Arts, and Mathematics), have also proven effective in improving science literacy.